A mediologia das práticas culturais: da transmissão à mise en scène da cultura tradicional no processo de festivalização - Thaise Valentim Madeira (2014)
This thesis is an analysis about the process of transformation of the festive quotidian practices, considered as traditional, in spectacular manifestations, in the present context of globalization. This evolutionary way between the feast and the festival is what we call the festivalization process.To make this analysis, we have studied two objects: the Festival Interceltique de Lorient, one of the biggest festivals in Europe, and the feasts of Kingdoms of Our Lady of Rosary, also called like Congado Mineiro, a religious celebration that happens in the state of Minas Gerais, Brazil.The Festival Interceltique de Lorient, the professional business of folklore in Brittany, produces a music 'model', exportable, adapted to modern society, and at the same time connected with the tradition. In parallel, the feasts of Kigdoms exposes a process already settled by the Festival Interceltique de Lorient: How a daily, family, religious and civil party is reworked gradually to become a spectacle, where authenticity and visibility become a conditional criterion for the existence of the feast and festival. With the Treze de Maio group, one of the representatives of this Kingdoms of Minas Gerais, we realise how the processes of transmission of the musical heritage are transmitted, and how the mise en scène of tradition takes shape. As a method of analysis, we look to the mediology of Regis Debray, which offers us ways to look and reflect about the symbolic elements that determine the dynamics of the feast and festivals, and the relations of these elements with the technical transmission of ideas, values and beliefs.